Herding to Market Consensus: An Empirical Investigation of its Presence in Nepal Stock Exchange (The Journal of Economic Concerns, 2022)
The study examines herd formation in Nepalese equity market. The study uses linear regression models including quadratic variant to model the relationship between return dispersion of individual scrips and aggregate market return for finding the herding behavior. The study does not find presence of herding. On the contrary, when presence of herding is tested for bearish and bullish trend, herd formation is detected in bullish trend. The study supports the notion that Nepalese equity market is prone to behavioral biases leading to pricing inefficiencies. The findings of the study can be helpful to make policies to protect retail investors from downside risk arising from these behavioral biases.